2017
DOI: 10.1177/0269881117699361
|View full text |Cite
|
Sign up to set email alerts
|

British Association for Psychopharmacology consensus guidance on the use of psychotropic medication preconception, in pregnancy and postpartum 2017

Abstract: Decisions about the use of psychotropic medication in pregnancy are an ongoing challenge for clinicians and women with mental health problems, due to the uncertainties around risks of the illness itself to mother and fetus/infant, effectiveness of medications in pregnancy and risks to the fetus/infant from in utero exposure or via breast milk. These consensus guidelines aim to provide pragmatic advice regarding these issues. They are divided into sections on risks of untreated illness in pregnancy; general pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
171
0
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 203 publications
(244 citation statements)
references
References 288 publications
(506 reference statements)
1
171
0
14
Order By: Relevance
“…The decision to use any pharmacological intervention during pregnancy is challenging for the mother in addition to the prescriber and requires clear knowledge of potential harmful effects on the developing fetus and risks such as the development of gestational diabetes. However, the choice to continue treatment or not can be overshadowed by the clinical need for therapy during gestation, and the potential consequences of withdrawing treatment …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The decision to use any pharmacological intervention during pregnancy is challenging for the mother in addition to the prescriber and requires clear knowledge of potential harmful effects on the developing fetus and risks such as the development of gestational diabetes. However, the choice to continue treatment or not can be overshadowed by the clinical need for therapy during gestation, and the potential consequences of withdrawing treatment …”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important given that recent reports in the UK have suggested that one in 25 women (aged 20–35 years), who die by suicide, do so during the perinatal periods (conception–pregnancy and postnatal) . And further, that poor mental health during gestation is highly correlated with poor mental health postnatally …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decision to use antidepressants during pregnancy should be based on the balance between risks and benefits, taking into account the severity of illness and psychiatric history. Recently, consensus guidelines have proven very useful to help healthcare professionals in clinical decision-making 15. It therefore appears appropriate that the different professionals involved (psychiatrists, general practitioner, gynaecologists, obstetrics) identify the depressive and/or anxious symptoms at an early stage or identify as soon as possible women who are at increased risk for perinatal depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…1 For other anti-epileptic and anti-epileptic mood stabilsers, carbamazepine can increase the risk of congenital malformations, but as lamotrigine is no longer strongly associated with cleft-palate or cleft-lip "it is the one of these three that we would feel more relaxed about prescribing during pregnancy", said Prof. McAlister-Williams.…”
Section: Professor Allan Youngmentioning
confidence: 99%